2014
DOI: 10.1097/hpc.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Successful Collaborative Model for STEMI Care Between a STEMI-Referral and a STEMI Receiving Center

Abstract: Streamlining STEMI patient care to reduce D2B is a major priority. We have demonstrated that establishing a transfer program between a STEMI-Referral Hospital (SRH) and SRC can markedly improve time to reperfusion. This approach has resulted in D12B that match or exceeds the D2B for nontransfer patients at most STEMI-receiving hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…The patients not referred had 4.6 times the odds of delay in receiving an ideal DTB time, even though it was not statistically significant. A study done in Chicago demonstrated that establishing a STEMI referral program between a secondary and tertiary care hospital with a cardiac catheterization lab facility would markedly improve the time to reperfusion [18].…”
Section: Discussionmentioning
confidence: 99%
“…The patients not referred had 4.6 times the odds of delay in receiving an ideal DTB time, even though it was not statistically significant. A study done in Chicago demonstrated that establishing a STEMI referral program between a secondary and tertiary care hospital with a cardiac catheterization lab facility would markedly improve the time to reperfusion [18].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the list of system practices may be incomplete. Third, additional factors not captured in our survey - such as collaborative relationships between EMS agencies, STEMI referral hospitals, and STEMI receiving centers 13,14 and decision-making processes at the STEMI referral hospital 15 – may influence DIDO and first-DTB times. Finally, our sample size may have been insufficient to detect a more subtle relationship between system practices and DIDO and FIRST-DTB times.…”
Section: Discussionmentioning
confidence: 99%